Tajweed game for children with autism: An interactive game for autism children to learn tajweed - Ramlan, Nadiah; Saidin , Maisarah; Hussin, Hayati (Jurnal Pendidikan Bitara UPSI, 2025)
Tajweed knowledge is very important in reciting the Quran.Teaching Tajweed faces specific hurdles during the delivery of education to children who have Autism Spectrum Disorder (ASD). Researchers developed a unique interactive system which was made for autistic students to learn the detailed specifications of Tajweed. The methodology utilizes multisensory learning principles as well as gamification techniques and adaptive technologies to implement visual, auditory and kinesthetic learning elements that optimize the mental and sensory processing needs of ASD children. This study employed a mixed-methods approach, involving 20 children aged 6 to 12 diagnosed with ASD, who participated in a 6-week intervention program consisting of twice-weekly 30-minute sessions. The presented approach receives a detailed description, including design specifications and implementation details, which prioritize evidence-based methods for addressing sensory differences alongside user-specific learning requirements. A pilot test of the educational method produced substantial improvements among participants, ranging from their involvement to their ability to understand and memorize Tajweed principles. Research results demonstrate that customized interactive learning systems create better possibilities for autistic children to learn the Quran effectively and find pleasure in their education. The research adds major importance to inclusive education by developing a new framework which combines classical religious instruction techniques with modern educational reform strategies. The finding carry profound implications for inclusive education, providing a clear mandate to develop policies that ensure the genuine integration of children with special needs into faith-based learning environments.